THE PHOENIX IS RISING AGAIN - Radić, Irena (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
The separation of company assets from the assets of its shareholders and the limited liability of company shareholders are two fundamental principles of company law. The principle of limited liability places a “corporate veil“ betweeen the company and its shareholders, protecting them from personal responsibility for corporate obligations. It also enables investors to limit their exposure to potential loss to their actual investment in company and to shift the risk of corporate insolvency to the business’s creditors. By creating incentives for business ventures, the“corporate veil“ of limited liability principle is beneficial to corporate shareholders and the society in general. However, it also opens the door for different kinds of abuses, one of which is embodied in the emergence of “phoenix“ companies. A “phoenix“ company is usually defined as a new company that arises from the ashes of its failed predcessor, taking over its assets and continuing its business, usually under the same or similar name, and with the same (de facto or de iure) controllers. The phenomenon of “phoenixism“ encompasses a range of activities, some of which are legitimate and lawful means of saving the business in financial distress, while others are illegal and constitute an abuse of the corporate limited liability form and the abuse of insolvency and tax law; there are also different shades of grey inbetween the two. The aim of this paper is to describe the conceptual framework of “phoenix“ companies, present the main indicators for detecting their activities, and categorise the various types of phoenix activity, with the aim of distinguishing between the harmful and beneficial “phoenixing“.
Keywords: phoenix companies; limited liability; abuse of corporate form; abuse of insolvency; tax avoidance